Evaluation of The Revitalization of Small Medium Industry Centers in Shopping Tourism in Tanggulangin, Kabupaten Sidoarjo - Paijatul Rohmah; Lukman Arif (Universitas Medan Area, 2022)
This article aims to analyze the Small and Medium Industry Center Revitalization Program for ICM on Shopping Tourism. The problem with the results of the revitalization program on shopping tourism that has been carried out by the Industry Service Office of Sidoarjo Regency. In order to approach this problem, the theory of Stufflebeam CIPP is used, namely Context, Input, Process, Product. The data were collected through observation, interview, and documentation techniques and analyzed qualitatively. The results of this study indicate; The context of planning for the ICM Center Revitalization for Shopping Tourism is based on the roadmaps of the Ministry of Industry by revitalizing the ICM Center Area for Shopping Tourism with eight indicators. The implementation input is assisted by the stakeholders; Public Works and Resources originating from the Special Allocation Fund. The evaluation process for the ICM Center Revitalization program on shopping tourism went well and smoothly, although there were several indicators that had not been implemented. Product achievements in the evaluation of the ICM center revitalization program on Shopping Tourism have an impact on the physical changes of the center but the increase in sales is still not felt. This study concludes that there are several indicators that have not been realized.